The Financial Strategy Instrument in the Context of Enterprise Modernization - G. ALEKSIN (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2019)
Problem of improving the strategic management quality at enterprise level (in particular its financial strategy formation and implementation) drastically increases under the recession conditions. It is highly important to take into account endogenous and exogenous factors influencing financial strategy formation, namely the issues raised due to need for modernization endemic to Ukraine’s real sector enterprises.The aim of the study is to determine financial strategy’s role in the context of the real sector’s modernization.The paper considers the problem of financial strategy development and implementation in the context of enterprise modernization in Ukraine. The author analyzes the problem of maintaining an enterprise’s strategic direction towards modernization though effective use of the financial strategy. The author studies the problem of financial management decisions’ nature in the context of enterprises’ innovative renewal. Based on the analysis of Ukrainian brewing industry enterprises, the paper provides practical recommendations considering financial strategy formation in the context of capital investment program implementation.Based on the evidence collected, the author arrived at a conclusion that different enterprises take different financial strategic decisions based on peculiarities of their external and internal environment. The author argued for the existence of a pattern concerning Ukraine’s real sector modernization issues, i. e. lack of a long-term focus, acute agency costs, weak interconnectedness of financing and operational policy. The author arrived at a conclusion that solutions to those issues are on both macro- and micro-level: firstly, state’s efforts to improve institutional environment, secondly, enterprises’ steps towards improving financing policy’s efficiency, thirdly, alignment of an enterprise’s financing policy and peculiarities of its exogenous and endogenous environment, which is highly important in the context of limited resources and uncertainty.